Self-supporting lithium-sulfur battery positive electrode based on MOFs (Metal-Organic Frameworks) mycelium-based carbon film and preparation method thereof
By using MOFs on the positive electrode of lithium sulfur battery to modify the mycelium carbon film, combined with the characteristics of mycelium fibers and MOFs, the shuttle effect and slow kinetics of lithium sulfur batteries are solved, and the specific capacity and rate performance of the battery are improved, and the simplification of the simplification of the battery is simultaneous. The preparation process is carried out and the cost is reduced.
Patent Information
- Application Number
- CN202411427467.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium sulfur batteries have affected their practical application due to the insulation and volume expansion of the active substance sulfur, the "shuttle effect" of polysulfides and the slow kinetic problems. Inadequate physical interactions lead to severe shuttle effects, limiting battery performance.
Modified the mycelium-based carbon film as the positive electrode of the self-supporting lithium-sulfur battery. By combining mycelium fibers and MOFs, the mycelium's sulfur storage, conductivity and mass transfer advantages are utilized, and the adsorption and catalytic capabilities of LiPSs through cobalt and nitrogen sites. , realize the effective combination of structure and function.
Improve the specific capacity and rate performance of lithium sulfur batteries, simplify the electrode preparation process, reduce production costs, and solve the problems of poor sulfur conductivity and volume changes through the high conductivity and large specific surface area of the porous carbon matrix, and improve the Overall performance of the battery.
Smart Images

Figure CN119230727A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur battery electrode materials, and in particular to a self-supporting lithium-sulfur battery positive electrode based on MOFs modified mycelium-based carbon film and a preparation method thereof. Background Art
[0002] With the storage demand for new energy and the endurance demand for power batteries, the existing energy storage system can no longer meet the needs of development, and it is urgent to develop energy storage systems with higher energy density and lower cost. Lithium-sulfur batteries (LSBs) have natural advantages in cost and energy density due to their ultra-high theoretical specific capacity (1675mAh / g) and theoretical energy density (2600Wh / L), abundant reserves of elemental sulfur, and environmental friendliness. However, lithium-sulfur batteries have serious problems such as the insulation and volume expansion of the active substance sulfur, the "shuttle effect" of polysulfides, and slow kinetics, which seriously affect the practical application of lithium-sulfur batteries. In addition, the non-polar carbon materials commonly used as positive electrode materials for lithium-sulfur batteries will cause serious shuttle effects during long-term cycles due to their weak physical interactions with polar polysulfides.
[0003] Metal organic frameworks (MOFs) are interconnected by coordination bonds of metal ions / clusters and organic ligands, with high crystallinity and long-range order. Due to their attractive features such as high specific surface area, adjustable pore size, topological structure, well-defined metal nodes and adjustable chemical composition, they have been proven to be new materials in electrochemical applications, and have been applied to LSB positive electrode electrocatalysts due to their strong adsorption capacity and high catalytic activity for LiPSs. However, the crystal size of MOFs is relatively small, and direct carbonization is more likely to aggregate into non-porous or microporous structures, which hinders the exposure of active sites, limits mass transfer and electrolyte penetration, and thus leads to performance degradation. By in situ growing MOFs on a suitable substrate, after heat treatment, the organic linkers in the MOFs precursor are converted to carbon, and the original framework will be retained, thereby generating materials with porous carbon structures. The generated MOFs-derived heteroatom-doped porous carbon-based composites always have the characteristics of high surface area, uniform distribution of active sites and excellent conductivity, which is conducive to mass transfer and rapid transfer of electrons and alleviates the shuttle effect.
[0004] At present, the key issue we are facing is to select suitable and excellent catalyst carriers that can both reasonably give play to the advantages of catalyst carriers and give full play to the polysulfide adsorption and catalytic capabilities of MOFs dual sites, and realize the effective combination of carrier structural characteristics and MOFs functional characteristics. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the present invention proposes a preparation method and application of a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film. This method combines mycelium and MOFs to not only give full play to the sulfur storage, conductivity, and mass transfer advantages of the mycelium carbon matrix, but also give full play to the LiPSs adsorption and catalytic ability of the cobalt and nitrogen sites, thereby realizing an effective combination of the mycelium structural characteristics and the MOFs functional characteristics.
[0006] A method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film comprises the following steps:
[0007] Step (1): selecting filamentous fungal species and preparing mycelium fibers using microbial culture technology;
[0008] Specifically, the potato dextrose agar (PDA) medium is prepared in proportion and dispensed into multiple test tubes, the fungal strains are transferred to the medium for expansion culture, and then the expanded cultured fungal strains are transferred to 200 mL of potato dextrose (PDB) culture solution for constant temperature shaking culture for a period of time to form a number of mycelial balls, and the fungal mycelial balls are collected after standing, washed with ionized water until neutral, and then crushed with a crusher to obtain mycelial fiber dispersion;
[0009] Step (2): loading the mycelium fiber dispersion with different MOFs dispersions by two loading methods: physical mixing and in-situ growth;
[0010] Step (3): vacuum filtering the mycelium fiber dispersion loaded with different MOFs onto filter paper, peeling off to obtain a composite mycelium membrane, flattening and freeze-drying to obtain a MOFs composite mycelium membrane;
[0011] Step (4): the MOFs composite mycelium membrane obtained in step (3) is cut with a cutter and neatly arranged between two graphite plates, placed in a tubular furnace, and subjected to a pre-carbonization and carbonization process under the protection of a reducing gas atmosphere to obtain a MOFs modified mycelium-based carbon membrane;
[0012] Step (5): The MOFs-modified mycelium-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table, and a DOL / DME mixed solution containing Li2S8 is added dropwise. After standing, a MOFs-modified mycelium-based carbon film-loaded sulfur self-supporting positive electrode is obtained, that is, a MOFs-modified mycelium-based carbon film self-supporting lithium-sulfur battery positive electrode.
[0013] Specifically, the filamentous fungi in step (1) include but are not limited to black mold, red mold, and penicillium; the diameter of the fungal mycelium ball is about 1 cm, and the diameter of the fungal mycelium fiber ranges from 2 to 7 μm.
[0014] In the step (1), the components of the culture medium of PDA are: potato extract powder, glucose, agar, chloramphenicol, and the ratio is 5.0:20.0:15.0:0.1; the components of the culture medium of PDB are: potato extract powder, glucose, chloramphenicol, and the ratio is 5.0:20.0:0.1. The constant temperature culture temperature is 25°C, and the shaking culture time is 72h.
[0015] Specifically, the two loading methods in step (2) are physical mixing and in-situ growth. Physical mixing is to mechanically stir and mix the mycelial fiber dispersion and the synthesized MOFs:
[0016] The mycelium fiber dispersion and MOFs are in a solute mass ratio of 100:1;
[0017] The MOFs and mycelium fiber dispersions obtained after magnetic stirring, ultrasound and aging of different metal salt solutions, organic ligands and capping agents are mixed, and magnetic stirring is used to disperse them evenly to obtain mycelium fiber dispersions loaded with different MOFs; in situ growth is to first mix the mycelium fiber dispersion with the metal salt solution and then magnetically stir it for 4 to 6 hours to allow the ions to adsorb onto the mycelium, and then add a certain amount of different organic ligands and perform ultrasound, magnetic stirring and aging to in situ grow MOFs particles on the mycelium fiber surface, thereby obtaining mycelium fiber dispersions loaded with different MOFs.
[0018] The metal salt type of the MOFs synthesis is chloride, nitrate or a combination of two, the corresponding metal types are Fe, Co, Ni, Zn, Cu, the capping agent is CTAB, PVP or a combination of two, the organic ligand is 2-methylimidazole, terephthalic acid or one or more combinations; the concentration range of the metal salt is 1 to 6 mmol, the concentration range of the organic ligand is 8 to 144 mmol, and the capping agent is 0.01 to 0.03 g; specifically, in the step (3), the filter paper is a hydrophobic nylon filter membrane with an average pore size of 0.22 μm, and the thickness of the mycelium membrane is between 40 and 400 μm; freeze-dried for 12 to 24 hours, the thickness of the MOFs composite mycelium membrane is 50 to 500 μm.
[0019] Specifically, the size of the cutting piece in step (4) is 16 to 20 mm; the temperature is increased and sintered, and the heating rate is controlled to be 2 to 10°C / min, 200 to 500°C low-temperature pre-decomposition is performed for 1 to 3 hours, and 700 to 900°C high-temperature sintering is performed for 2 to 4 hours; the thickness of the conductive skeleton of the MOFs-modified mycelium-based carbon film is 40 to 400 μm.
[0020] Specifically, in step (5), the rotation speed of the rotating table is 150 rad / min, 20 to 200 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1).
[0021] The self-supporting lithium-sulfur battery positive electrode of MOFs-modified mycelium-based carbon film is used to assemble button cells, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs-modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode → gasket → shrapnel → positive electrode shell, thus obtaining a lithium-sulfur battery using a MOFs-modified mycelium-based sulfur-loaded self-supporting positive electrode.
[0022] Beneficial effects of the present invention:
[0023] The present invention provides a preparation method of MOFs modified mycelium-based carbon film and its energy storage application as a positive electrode of a lithium-sulfur battery after being loaded with sulfur, which has the following beneficial effects:
[0024] (1) The mycelium selected in the present invention grows rapidly, has good ball-forming performance, has a three-dimensional cross-linked network structure, and has a large specific surface area. The hydroxyl groups in the chitin of its cell wall can adsorb metal ions. The two are combined as a self-supporting material. The preparation method is simple and no additional binder or conductive agent is required. The production cost is low, the raw material source is wide, and the biocompatibility is good. It is an effective example of using renewable biomaterials to achieve sustainable development, and it brings hope to the development and application of lithium-sulfur batteries.
[0025] (2) The present invention utilizes the special structural characteristics of the biomass soft template to form a cross-linked network fiber structure after carbonization, so that the MOFs particles on it have a large growth space, providing an effective channel for the infiltration of the electrolyte and the electron transmission. The MOFs modified mycelium-based carbon film self-supporting cathode material prepared in this way has good rate performance;
[0026] (3) The present invention uses mycelium fibers with a three-dimensional cross-linked network structure as an ideal matrix for in-situ anchoring of MOFs, and the rich heteroatom doping such as N, P, and S can fully expose active sites and promote ion adsorption and migration. Combining mycelium with MOFs can not only give play to the sulfur storage, conductivity, and mass transfer advantages of mycelium carbon matrix, but also give play to the LiPSs adsorption and catalytic ability of cobalt and nitrogen sites, realizing the effective combination of mycelium structural characteristics and MOFs functional characteristics.
[0027] (4) The present invention shows that an excellent sulfur carrier should have both structural advantages and catalytic activity. A porous carbon matrix with high conductivity and large specific surface area can solve the problem of poor conductivity of S / Li2S and volume change during the conversion process between the two, and an integrated self-supporting carbon matrix can further increase the sulfur loading. Therefore, a self-supporting carbon matrix is an advantageous structure for dealing with positive electrode defects.
[0028] (5) The self-supporting electrode prepared by the present invention through a simple biological culture, freeze drying, and high-temperature carbonization process does not require additional binders, conductive agents, and current collectors compared to aluminum foil-based slurry-coated electrodes and can be directly used as electrodes, which not only improves the positive electrode specific capacity but also simplifies the electrode preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are SEM images of the MOFs-modified mycelium-based membrane in Example 2 of the present invention, wherein (a) and (c) represent SEM images of the MOFs-modified mycelium-based membrane before carbonization, and (b) and (d) represent SEM images of the MOFs-modified mycelium-based membrane after carbonization.
[0030] Figure 2 This is a 5000-fold EDS image of the MOFs-modified mycelium-based carbon film in Example 1 of the present invention.
[0031] Figure 3 This is a charge and discharge curve diagram of the MOFs modified mycelium-based carbon film self-supporting positive electrode in Example 4 of the present invention.
[0032] Figure 4 This is a graph of the rate performance of the MOFs-modified mycelium-based carbon film self-supporting positive electrode in Examples 1-4 of the present invention.
[0033] Figure 5 This is a long cycle performance diagram of the MOFs modified mycelium-based carbon film self-supporting positive electrode in Example 3 of the present invention after 50 cycles at 0.1C. DETAILED DESCRIPTION
[0034] The following will be combined with the attached embodiment of the present invention Figure 1-5 As shown, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] Step (1): Select a Penicillium chrysogenum strain and prepare mycelium fibers using microbial culture technology, specifically: prepare a PDA culture medium in proportion and distribute it in multiple test tubes, transfer the fungal strain to the culture medium for expansion culture, and then transfer the expanded cultured fungal strain to a conical flask containing 200 mL of PDB culture solution for constant temperature shaking culture at 25° C. for 24 hours. The mycelium balls of Penicillium chrysogenum grow to a diameter of about 1 cm, stand and collect, wash with ionized water until neutral, and then crush with a crusher to obtain a Penicillium chrysogenum mycelium fiber dispersion. The diameter of the Penicillium chrysogenum mycelium fiber ranges from 2 to 5 μm.
[0037] The components of the culture medium for PDA are potato extract powder, glucose, agar, and chloramphenicol in a ratio of 5.0:20.0:15.0:0.1; the components of the culture medium for PDB are potato extract powder, glucose, and chloramphenicol in a ratio of 5.0:20.0:0.1;
[0038] Step (2): The mycelium fiber dispersion obtained in step (1) is loaded with ZIF-67 by an in-situ growth loading method, 1 mmol Co(NO3)2·6H2O is added to the solution obtained in step (1), magnetically stirred for 6 hours, then 8 mmol 2-MI and 0.01 g CTAB are added, ultrasonicated for 30 minutes, magnetically stirred for 60 minutes, and aged for 12 hours to obtain a mycelium fiber dispersion loaded with ZIF-67.
[0039] Step (3): The mycelium fiber dispersion loaded with ZIF-67 obtained in step (2) is vacuum filtered onto filter paper, flattened, pre-frozen on a culture dish, and freeze-dried for 12 hours to obtain a ZIF-67 composite mycelium membrane with a thickness of 50 μm.
[0040] Step (4): The ZIF-67 composite mycelium membrane obtained in step (3) is cut into ZIF-67 composite mycelium membrane sheets with a diameter of 16 mm by a cutter, and the sheets are neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and heated and sintered in a reducing atmosphere furnace, with the heating rate controlled at 5°C / min, low-temperature pre-decomposition at 200°C for 1h, and high-temperature sintering at 700°C for 2h; the thickness of the conductive skeleton of the obtained ZIF-67 modified mycelium-based carbon membrane is 40μm.
[0041] Step (5): The ZIF-67 modified mycelium-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1). After standing, a ZIF-67 modified mycelium-based carbon film-loaded sulfur self-supporting positive electrode is obtained.
[0042] Step (6): Assemble the ZIF-67 modified mycelium-based carbon film sulfur-supported self-supporting positive electrode into a button cell, wherein the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs modified mycelium-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining a lithium-sulfur battery using a ZIF-67 modified mycelium-based sulfur-supported self-supporting positive electrode.
[0043] The electrochemical performance test of the ZIF-67 modified mycelium-based carbon film self-supporting cathode prepared in Example 1 proved its excellent electrochemical performance as a framework material. Figure 4 As shown in the figure, the first discharge specific capacity of nearly 1260mAh / g, 1057mAh / g, 912mAh / g and 865mAh / g were respectively exhibited at current densities of 0.1C, 0.2C, 0.5C and 1C. When the current density returned to 0.1C, the positive electrode discharge specific capacity could reach 1133mAh / g, indicating that the ZIF-67 modified mycelium-based membrane has excellent rate performance. Figure 2 As shown, after high-temperature carbonization, C, N, O, and Co are evenly distributed on the mycelium carbon skeleton, indicating that the metal Co and N elements are successfully introduced and cooperate well with the carbon skeleton.
[0044] Example 2
[0045] Step (1): selecting a Rhizopus stolonifer strain, and preparing mycelium fiber by using microbial culture technology, specifically: configuring PDA culture medium in proportion and dispensing it into multiple test tubes, transferring the fungal strain to the culture medium for expansion culture, and then transferring the expanded cultured fungal strain to a conical flask containing 200 mL of PDB culture solution for constant temperature 25° C. shaking culture for 24 hours, and growing the Rhizopus stolonifer mycelium ball to a diameter of about 1 cm, collecting it after standing, washing it with ionized water until it is neutral, and then crushing it with a crusher to obtain a Rhizopus stolonifer mycelium fiber dispersion, wherein the diameter of the Rhizopus stolonifer mycelium fiber ranges from 4 to 7 μm.
[0046] The components of the culture medium for PDA are potato extract powder, glucose, agar, and chloramphenicol in a ratio of 5.0:20.0:15.0:0.1; the components of the culture medium for PDB are potato extract powder, glucose, and chloramphenicol in a ratio of 5.0:20.0:0.1;
[0047] Step (2): The mycelial fiber dispersion of Rhizopus stolonifer obtained in step (1) is loaded with ZIF-8 by an in-situ growth loading method, 1 mmol Zn(NO3)2·6H2O is added to the solution obtained in step (1), magnetically stirred for 6 hours, and then 8 mmol 2-MI and 0.02 g CTAB are added, ultrasonicated for 30 minutes, magnetically stirred for 60 minutes, and aged for 12 hours to obtain a mycelial fiber dispersion loaded with ZIF-8.
[0048] Step (3): The mycelium fiber dispersion loaded with ZIF-8 obtained in step (2) is vacuum filtered onto filter paper, peeled off and flattened on a culture dish for pre-freezing, and freeze-dried for 12 hours to obtain a ZIF-8 composite mycelium membrane with a thickness of 100 μm.
[0049] Step (4): The ZIF-8 composite mycelium membrane obtained in step (3) is cut into ZIF-8 composite mycelium membrane sheets with a diameter of 16 mm by a cutter, and the sheets are neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and heated and sintered in a reducing atmosphere furnace, with the heating rate controlled at 10°C / min, low-temperature pre-decomposition at 200°C for 3h, and high-temperature sintering at 800°C for 3h; the thickness of the conductive skeleton of the obtained ZIF-8 modified mycelium-based carbon membrane is 80μm.
[0050] Step (5): The ZIF-8 modified mycelium-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 40 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1). After standing, a ZIF-8 modified mycelium-based carbon film-loaded sulfur self-supporting positive electrode is obtained.
[0051] Step (6): Assemble the ZIF-8 modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode into a button cell, wherein the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → ZIF-8 modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining a lithium-sulfur battery using a ZIF-8 modified mycelium-based sulfur-loaded self-supporting positive electrode.
[0052] The morphology of the ZIF-8 modified mycelium-based precursor and sintered body prepared in Example 2 is as follows: Figure 1 (a) Figure 1 (b) Figure 1 (c) Figure 1 As shown in (d), before sintering, ZIF-8 crystals were successfully loaded on the surface of the mycelium pores, and the surface of the ZIF-8 nanoparticles was smooth and had a granular cubic structure. The particle size of ZIF-8 was about 600-900nm. After sintering, ZIF-8 was successfully converted into Zn nanoparticles, and the ZIF-8 skeleton collapsed to form Zn / N@PCCF with the mycelium. Figure 3 As shown, the electrochemical performance of the ZIF-8 modified mycelium-based carbon film self-supporting positive electrode prepared in Example 4 was tested, and the discharge capacity at 0.1C in the first week was 1322.2 mAh / g.
[0053] Example 3
[0054] Step (1): selecting an Aspergillus niger strain and preparing mycelium fiber by using microbial culture technology, specifically: configuring a PDA culture medium in proportion and dispensing it into multiple test tubes, transferring the fungal strain to the culture medium for expansion culture, and then transferring the expanded cultured fungal strain to a conical flask containing 200 mL of PDB culture solution for constant temperature 25° C. shaking culture for 24 hours, until the Aspergillus niger mycelium ball grows to a diameter of about 1 cm, standing and collecting it, washing it with ionized water until it is neutral, and then crushing it with a crusher to obtain an Aspergillus niger mycelium fiber dispersion, wherein the diameter of the Aspergillus niger mycelium fiber ranges from 2 to 7 μm.
[0055] The components of the culture medium for PDA are potato extract powder, glucose, agar, and chloramphenicol in a ratio of 5.0:20.0:15.0:0.1; the components of the culture medium for PDB are potato extract powder, glucose, and chloramphenicol in a ratio of 5.0:20.0:0.1;
[0056] Step (2): The Aspergillus niger mycelium fiber dispersion obtained in step (1) is loaded with MIL-53 (Fe) by an in-situ growth loading method, 3 mmol FeCl3·6H2O is added to the solution obtained in step (1), magnetic stirring is performed for 5 hours, and then 24 mmol terephthalic acid is added, ultrasonication is performed for 40 minutes, magnetic stirring is performed for 30 minutes, and aging is performed for 18 hours to obtain a mycelium fiber dispersion loaded with MIL-53 (Fe).
[0057] Step (3): Vacuum filter the mycelium fiber dispersion loaded with MIL-53 (Fe) obtained in step (2) onto filter paper, peel it off and flatten it on a culture dish for pre-freezing, and freeze-dry it for 12 hours to obtain a MIL-53 (Fe) composite mycelium film with a thickness of 200 μm.
[0058] Step (4): The MIL-53 (Fe) composite mycelium membrane obtained in step (3) is cut into MIL-53 (Fe) composite mycelium membrane sheets with a diameter of 20 mm by a cutter, and the sheets are neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and heated and sintered in a reducing atmosphere furnace. The heating rate is controlled to be 2°C / min, and the low-temperature pre-decomposition is performed at 400°C for 2h, and the high-temperature sintering is performed at 900°C for 4h. The thickness of the conductive skeleton of the obtained MIL-53 (Fe) modified mycelium-based carbon membrane is 160μm.
[0059] Step (5): The MIL-53 (Fe) modified mycelium-based carbon film obtained in step (4) was placed in a glove box, fixed on a rotating table at a speed of 150 rad / min, and 100 μL of a 0.2 g / mL Li2S8 solution was added dropwise, and the solvent was a mixed solution of DOL / DME (v:v=1:1). After standing, a MIL-53 (Fe) modified mycelium-based carbon film-supported sulfur self-supporting cathode was obtained.
[0060] Step (6): Assemble the MIL-53 (Fe) modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode into a button cell, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg (s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg (s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MIL-53 (Fe) modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode → gasket → spring → positive electrode shell, so as to obtain a lithium-sulfur battery using a MIL-53 (Fe) modified mycelium-based sulfur-loaded self-supporting positive electrode.
[0061] The electrochemical performance of the MIL-53 (Fe) modified mycelium-based carbon film self-supporting cathode prepared in Example 3 was tested. Figure 5 It is shown that after 50 cycles at a current density of 0.1C, the capacity is still maintained at about 936mAh / g, and the single-cycle decay rate is 0.56%. The battery before cycling has a small charge transfer impedance, indicating that it has fast charge transfer kinetics, which is attributed to the three-dimensional cross-linked carbon skeleton structure of the hyphae and the highly conductive Fe metal, which can synergistically enhance the electrolyte penetration and charge transfer between the active material and the positive electrode skeleton.
[0062] Example 4
[0063] Step (1): Select a Mucor species and prepare mycelium fiber using microbial culture technology, specifically: PDA culture medium is configured in proportion and divided into multiple test tubes, the fungal species is transferred to the culture medium for expansion culture, and then the expanded cultured fungal species is transferred to a conical flask containing 200 mL of PDB culture solution for constant temperature 25° C. shaking culture for 24 hours. The Mucor mycelium ball grows to a diameter of about 1 cm, and after standing and collecting, it is washed with ionized water to neutrality, and then crushed with a crusher to obtain a Mucor mycelium fiber dispersion. The diameter of the Mucor mycelium fiber ranges from 4 to 7 μm.
[0064] The components of the culture medium for PDA are potato extract powder, glucose, agar, and chloramphenicol in a ratio of 5.0:20.0:15.0:0.1; the components of the culture medium for PDB are potato extract powder, glucose, and chloramphenicol in a ratio of 5.0:20.0:0.1;
[0065] Step (2): The Mucor mycelium fiber dispersion obtained in step (1) is loaded by mechanical mixing, 6 mmol Ni(NO3)2·6H2O, 144 mmol 2-MI and 0.03 g CTAB are magnetically stirred for 3 hours, aged for 12 hours, and then the obtained Ni-MOF solution and mycelium fiber dispersion are mixed and magnetically stirred for 3 hours to obtain a mycelium fiber dispersion loaded with Ni-MOF.
[0066] Step (3): The Ni-MOF loaded mycelium fiber dispersion obtained in step (2) is vacuum filtered onto filter paper, peeled off and flattened on a culture dish for pre-freezing, and freeze-dried for 12 hours to obtain a Ni-MOF composite mycelium membrane with a thickness of 500 μm.
[0067] Step (4): The Ni-MOF composite mycelium membrane obtained in step (3) is cut into Ni-MOF composite mycelium membrane sheets with a diameter of 16 to 20 mm by a cutter, and the sheets are neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and heated and sintered in a reducing atmosphere furnace, with the heating rate controlled at 2°C / min, 500°C low-temperature pre-decomposition for 2h, and 900°C high-temperature sintering for 4h; the thickness of the conductive skeleton of the obtained Ni-MOF modified mycelium-based carbon membrane is 400μm.
[0068] Step (5): The Ni-MOF modified mycelium-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 200 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1). After standing, a Ni-MOF modified mycelium-based carbon film-loaded sulfur self-supporting positive electrode is obtained.
[0069] Step (6): Assemble the Ni-MOF modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode into a button cell, wherein the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) of a DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → Ni-MOF modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining a lithium-sulfur battery using a Ni-MOF modified mycelium-based sulfur-loaded self-supporting positive electrode.
[0070] The electrochemical performance of the Ni-MOF modified mycelium-based carbon film self-supporting cathode prepared in Example 4 was tested. Figure 3 From the constant current charge-discharge curves of the first week at 0.1C, it can be seen that the Ni-MOF modified mycelium-based carbon film self-supporting positive electrode has two typical discharge platforms and one charging platform. The voltage platform around 2.3V corresponds to the transformation of S8 to long-chain LiPSs, and the 2.1V platform corresponds to the transformation of long-chain LiPSs to Li2S. The charging platform around 2.4V is the reverse reaction of the above reaction, that is, the oxidation reaction of Li2S to S8.
[0071] The above results can all illustrate that the MOFs modified mycelium-based carbon film self-supporting positive electrode prepared by the present invention is good, is a promising self-supporting positive electrode material for lithium-sulfur batteries, and can greatly improve the battery performance of lithium-sulfur batteries. Biomass mycelium is used as a raw material, dispersed by mechanical crushing and stirring, loaded with metal atoms as metal active centers, organic ligands as framework materials, and filtered to form a film, and then a MOFs modified mycelium-based precursor is prepared by freeze drying. The freeze-dried mycelium film is sandwiched between two graphite plates, placed in a tubular furnace, and nitrogen is used as a protective gas. The mycelium fiber-based self-supporting electrode material is obtained by step-by-step heating. In the present invention, mycelium fibers are interwoven with each other, and the composite material is thinner and has better support. The mycelium fibers used in the present invention can be regenerated in large quantities biologically, are cheap and easy to obtain, and the obtained self-supporting positive electrode sheet adopts a stacked assembly battery, and the battery performance test has good rate performance.
[0072] The rate performance results obtained in Examples 1-4 are compared with the results of the reference patent [1] (Yan Yinglin, Yang Yuanyuan, et al. Preparation method, application and preparation of mycelium-based carbon film conductive skeleton.) as shown in Table 1. In summary, Example 1 is the best sample group with excellent electrochemical performance. MOFs crystals are uniformly loaded. A large number of uniform MOFs-derived carbon skeletons on the mycelium surface further enrich the specific surface area and pore structure of the mycelium carbon matrix, providing a large number of defect sites for loading and converting sulfur. The MOFs-derived carbon material can also fully expose Co catalytic sites and nitrogen doping sites, which can more effectively chemically adsorb and catalyze LiPSs conversion and improve its conversion kinetics.
[0073] Table 1 Comparison of chemical properties of Examples 1-4 and reference patent [1]
[0074]
Claims
1. A method for preparing a self-supporting lithium-sulfur battery positive electrode of MOFs modified mycelium-based carbon film, characterized in that: The following steps are involved: Step (1): PDA culture medium is prepared in proportion and divided into multiple test tubes, fungal strains are transferred to the culture medium for expansion culture, and then the expanded cultured fungal strains are transferred to a conical bottle containing PDB culture medium for constant temperature shaking culture for a period of time to form a number of mycelium balls, and the fungal mycelium balls are collected after standing, washed with ionized water until neutral, and then crushed with a crusher to obtain mycelium fiber dispersion; Step (2): loading the mycelium fiber dispersion with different MOFs dispersions by two loading methods: physical mixing and in-situ growth; Step (3): vacuum filtering the mycelium fiber dispersion loaded with different MOFs onto filter paper, peeling off to obtain a composite mycelium membrane, sandwiching it between two layers of culture dishes, and then pressing an iron block with a mass within a quantitative range on the culture dishes, freeze-drying, and obtaining a MOFs composite mycelium membrane; Step (4): cutting the MOFs composite mycelium membrane obtained in step (3) into MOFs composite mycelium membrane sheets with a cutter, sandwiching them neatly between two graphite plates, placing them in a tubular furnace, and performing pre-carbonization and carbonization processes under the protection of a reducing gas atmosphere to obtain a MOFs modified mycelium-based carbon membrane; Step (5): The MOFs-modified mycelium-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table, and a DOL / DME mixed solution containing Li2S8 is added dropwise. After standing, a MOFs-modified mycelium-based carbon film-loaded sulfur self-supporting positive electrode is obtained, that is, a MOFs-modified mycelium-based carbon film self-supporting lithium-sulfur battery positive electrode.
2. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: The diameter of the fungal mycelium ball in step (1) is about 1 cm, and the diameter of the microbial mycelium fiber ranges from 2 to 7 μm.
3. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: In the step (1), the components of the culture medium of PDA are: potato extract powder, glucose, agar, chloramphenicol, and the ratio is 5.0:20.0:15.0:0.1; the components of the culture medium of PDB are: potato extract powder, glucose, chloramphenicol, and the ratio is 5.0:20.0:0.1; the constant temperature culture temperature is 25°C, and the shaking time is 24 hours.
4. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: The two loading methods in step (2) are physical mixing and in-situ growth. Physical mixing is to mechanically stir and mix the mycelium fiber dispersion and the synthesized MOFs. The mycelium fiber dispersion and MOFs are in a solute mass ratio of 100:1; The MOFs and mycelium fiber dispersions obtained by magnetically stirring, ultrasonicating and aging different metal salt solutions, organic ligands and capping agents are mixed, and the mycelium fiber dispersions loaded with different MOFs are obtained after magnetic stirring to make them dispersed evenly; In situ growth is to first mix the mycelium fiber dispersion with the metal salt solution and then magnetically stir it for 4 to 6 hours to allow the ions to adsorb onto the mycelium. Then, a certain amount of different organic ligands are added and ultrasonicated, magnetically stirred, and aged to grow MOFs particles in situ on the mycelium fiber surface, thereby obtaining a mycelium fiber dispersion loaded with different MOFs.
5. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 4, characterized in that: The metal salt types for synthesizing MOFs are chlorides, nitrates or a combination of two, the corresponding metal types are Fe, Co, Ni, Zn, and Cu, the capping agent is CTAB, PVP or a combination of two, and the organic ligand is 2-methylimidazole, terephthalic acid or a combination of one or more; the concentration range of the metal salt solution is 1-6 mmol, the concentration range of the organic ligand is 8-144 mmol, and the capping agent is 0.01 to 0.13 g.
6. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: In the step (3), the filter paper is a hydrophobic nylon filter membrane with an average pore size of 0.22 μm. When the composite mycelium membrane is sandwiched between the culture dishes, it is necessary to apply plastic wrap on the top and bottom. The mass of the iron block pressing the culture dish is 500 g. -1 The thickness of the mycelium film is between 40 and 400 μm after freeze drying for 12 to 24 h, and the thickness of the MOFs composite mycelium film is between 50 and 500 μm.
7. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: The size of the cutting pieces in step (4) is 16 to 20 mm; the temperature is increased and sintered, and the heating rate is controlled to be 2 to 10°C / min, 200 to 500°C low-temperature pre-decomposition is performed for 1 to 3 hours, and 700 to 900°C high-temperature sintering is performed for 2 to 4 hours; the thickness of the conductive skeleton of the MOFs-modified mycelium-based carbon film is 40 to 400 μm.
8. The method for preparing a self-supporting lithium-sulfur battery positive electrode of a MOFs-modified mycelium-based carbon film according to claim 1, characterized in that: In the step (5), the rotation speed of the rotating table is 150 rad / min, and 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1).
9. The self-supporting lithium-sulfur battery positive electrode of the MOFs-modified mycelium-based carbon film prepared by the method according to any one of claims 1 to 8 is used to assemble a button battery, characterized in that: The assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs modified mycelium-based carbon film sulfur-loaded self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining a lithium-sulfur battery using a MOFs modified mycelium-based sulfur-loaded self-supporting positive electrode.
Citation Information
Patent Citations
Method for growing MOF by using bacteria as template to prepare multi-stage porous carbon material and application of multi-stage porous carbon material in energy storage devices
CN110745806A
MOF-modified cellulosic material intermediate layer for lithium-sulfur battery and preparation method
CN112391700A
Preparation method and application of mycelium-based carbon film conductive skeleton and method for preparing battery
CN114188540A
BC loaded ZIF-67 derived CNF / CoS-Co9S8-NC composite material as well as preparation and application methods thereof
CN116715277A
Method for culturing edible fungus hyphae by using white spirit byproduct pot-bottom water
CN118556550A
Cited By
Self-supporting composite electrode for CDI as well as preparation method and application of self-supporting composite electrode
CN120441037A
